Design and Performance of an Integrated Envelope/Lighting System - Eleanor S. Lee; Stephen E. Selkowitz (ICBEST '97 International Conference on Building Envelope Systems and Technology, 1997)
Dynamic envelope/lighting systems offer the potential to achieve a near optimum energy-efficient environment meeting occupant needs throughout the year by adapting to dynamic meteorological conditions and changing occupant preferences in real time. With the dramatic increased functionality of the microprocessor, there is an untapped potential to make dynamic envelope/lighting systems easier to use, diagnose, and monitor, and to integrate them as part of a sophisticated building-wide control system. This study addresses the complex relationship between this energy-efficiency technology and many of the non-energy issues related to its potential acceptance by the building industry, architects, owners, and users. We demonstrate the concept of integrated dynamic systems with a prototype motorized venetian blind operated in synchronization with electric lighting and daylighting controls via an intelligent control system. Research work conducted with simulation software and reduced-scale and full-scale field tests is summarized. Much of this work is directly relevant to other active shading and daylighting systems on the market today and to state-of-the-art window systems yet to come (i.e., electrochromics).